Alternative pathways to climate change adaptation and disaster risk reduction mainstreaming and integration in development planning and budgeting of local government units - Magalang, Miguel; Jo, Arvin; La Vina, Antonio; Marinduque Council for Environmental Concerns; Atebeo School of Government; Manila Observatory; Coastal Core Sorsogon; Aksyon Kilma Pilipinas; Regional Climate Change Adaptation Platform for Asia. ([Manila] Marinduque Council for Environmental Concerns (MACEC) ... [et al.], 2012)
This toolkit is an output of the Adaptation Knowledge Platform?s (AKP) capacity building activities in the Philippines. AKP and its country partner, the Ateneo School of Government (ASoG), facilitated a knowledge building process to enable them to: (1) raise the level of awareness of, and sharpen approaches to climate change adaptation (CCA); and (2) adopt a more transdisciplinary approach in crafting local development plans of the Albay and Iloilo provinces in the Philippines. As part of the process, AKP and ASoG carried out a series of learning dialogues in May 2012. This comprehensive toolkit incorporates findings from these dialogues and presents practitioners a twelve-step process guide to mainstreaming CCA and DRR into development planning.
Foreword -- Definition of terms -- Introduction -- 12 steps in mainstreaming climate change adaptation and disaster risk Reduction in development planning: a practitioner's perspective -- Sample tools.
Keywords: Climatic changes -- Environmental aspects -- Philippines; Environmental risk assessment -- Philippines; Risk assessment -- Environmental aspects -- Philippines; Climatic changes -- risk assessment -- Philippines; Environmental law -- compliance cost -- Philippines